No more legend to print. Sur quelques hantises de No Country for Old Men - Lambert Barthélémy (Revue LISA)
This article singles out just a few of the obsessive traces on which McCarthy's narrative is built. While it is initially a question of radical violence and offers a critical rereading of the imaginary of the frontier, it also examines the textual obsessions and the very close relationship that No Country for Old Men maintains with Tom Sawyer and King Lear. This powerful intertextual dynamic makes it possible to weave together ethics, politics and economics in order to give an unvarnished description of the state of anomy reached by an advanced capitalist society, of the ineffectiveness of the ideological narratives that found it, and of disunion as the inescapable correlate of mass consumption and global addictions.